Postoperative Stiffening after Bicruciate-Retaining Total Knee Arthroplasty - Lavoie, Frédéric; Al-Shakfa, Fidaa; Moore, James Reuben; Mychaltchouk, Lydia; Iguer, Khaled (The Journal of Knee Surgery, 2018)
Bicruciate-retaining (BCR) total knee arthroplasty (TKA) has recently experienced a resurgence of popularity. It may be a good option among a younger, more active population because it restores knee kinematics better than other prosthetic designs. Results obtained in the first 100 BCR TKAs implanted with a simplified gap-balancing technique are reported, with special attention paid to knee flexion, through comparison with a cohort of 100 posterior-stabilized (PS) TKAs. We conducted a retrospective comparative cohort study of 100 BCR TKAs (90 patients) and 100 PS TKAs (88 patients). Knees with a BCR TKA lost significantly more flexion PS TKA in the early postoperative period when their preoperative flexion was less than 130 degrees (loss of 40 degrees vs. loss of 24 degrees). Postoperative range of motion was similar between BCR TKA and PS TKA when preoperative knee flexion was 130 degrees or more, and when there was no preoperative flexion contracture. Postoperative stiffening seems to be more frequent and of greater magnitude after BCR TKA, compared with PS TKA, in patients suffering from preoperative flexion stiffness. Further investigation on the causes of this phenomenon is warranted.
Keywords: total knee arthroplasty; anterior cruciate ligament; stiffening; knee flexion; arthrofibrosis